Evaluation of cattle fattening results on one large scale farm - Kiss, Martin; Holló, Gabriella (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The authors evaluated the key indicators of large-scale, intensive cattle fattening system based on the evaluation of fattening performance of bulls from different cattle breeds. In this study, the data of 551 individuals of five breeds (Simmental (SIM): 236, Limousin (LIM): 115, Charolais (CH): 94, Angus (A) 77, Blonde d’aquitaine (B): 29) from years between 2019-2020 were analysed. According to the fattening results, A bulls were introduced to the farm at the youngest age, while the oldest one were CH bulls. A had the smallest initial live weight (217 kg), contrary to B, they had the largest one (245 kg). The final fattening weight ranged from 343 to 365 kg. The highest daily gain during fattening was detected for CH (1731 g/day), whilst SIM breed had the highest live weight gain during lifetime (1215 g/day). The muscularity score of A and B bulls was changed from the R category to the U category, while the decisive part of the CH and LIM bulls was reclassified from U to E category at the end of fattening period. The muscularity of the SIM remained R-rated, but most of them were transferred to the more favorable R + subcategory. At the same initial live weight, the daily gain of fattening bulls younger than 10 months is significantly lower than that of bulls purchased at a later age (older than 10 months).
Keywords: cattle; fattening; weight gain; muscularity category